Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1748-720x.2010.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of Legal Services for Criminalized Populations: The Case of People Who Use Drugs, Sex Workers and Sexual and Gender Minorities

Abstract: Social exclusion and legal marginalization are important determinants of health outcomes for people who use illicit drugs, sex workers, and persons who face criminal penalties because of homosexuality or transgenderism. Incarceration may add to the health risks associated with police repression and discrimination for these persons. Access to legal services may be essential to positive health outcomes in these populations. Through concrete examples, this paper explores types of legal problems and legal services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…Both contain extensive discussion of equity which is, in some ways, connected to a human rights understanding of equality and nondiscrimination, but this is mainly in relation to economic and geographic inequities and their role in producing vulnerability and disadvantage. While this overlaps with the prohibition on discrimination in international human rights law based on property or economic grounds, it leaves out the myriad other prohibited manifestations of inequality and discrimination which have been shown to impact health (Csete and Cohen 2010). For example, ethnicity has been documented as an important determinant of inequities in child survival outcomes (Mulholland et al 2008).…”
Section: Equality and Non-discriminationmentioning
confidence: 98%
See 1 more Smart Citation
“…Both contain extensive discussion of equity which is, in some ways, connected to a human rights understanding of equality and nondiscrimination, but this is mainly in relation to economic and geographic inequities and their role in producing vulnerability and disadvantage. While this overlaps with the prohibition on discrimination in international human rights law based on property or economic grounds, it leaves out the myriad other prohibited manifestations of inequality and discrimination which have been shown to impact health (Csete and Cohen 2010). For example, ethnicity has been documented as an important determinant of inequities in child survival outcomes (Mulholland et al 2008).…”
Section: Equality and Non-discriminationmentioning
confidence: 98%
“…For example, where same-sex sexual activity is criminalised, evidence has shown that people may avoid relevant services out of fear that their sexual activities and partners will be discovered and reported to the police (Gruskin and Ferguson 2009). Other areas where laws and policies have a direct bearing on the successful functioning of a health system and, therefore, could usefully be considered include: residency requirements surrounding access to health services, criminalisation of sex work, age of consent laws and other constraints around young persons' access to sexual and reproductive health services and family law Ferguson 2009, Csete andCohen 2010). Awareness of the existence of these laws, and their subsequent reform, would make important contributions to the health of many and to the overall effectiveness of health system efforts.…”
Section: Legal and Policy Context: Moving Beyond Regulationmentioning
confidence: 99%
“…Training for police and judges, and court accompaniment for sex workers charged with crimescan also provide access to justice for sex workers. 110 In South Africa, sex workers can receive paralegal training on due process and sex worker rights, to ensure sex workers’ rights are upheld throughout the legal process. 111 These examples again illustrate the value of investing in sex worker organizing and partnership with legal and criminal justice sectors to support health and human rights.…”
Section: Evidence-based Reform: the Human Rights Framework For Changementioning
confidence: 99%
“…Lastly, ensuring access to legal services among IDU is important in order to help victims of police abuse obtain redress and compensation in this setting. In addition, a recent review indicated that expanded legal services also have potential to prevent police abuse and promote health benefits among IDU [41]. …”
Section: Discussionmentioning
confidence: 99%